2017
DOI: 10.21037/jtd.2017.06.03
|View full text |Cite
|
Sign up to set email alerts
|

Screening for obstructive sleep apnea syndrome in asthma patients: a prospective study based on Berlin and STOP-Bang questionnaires

Abstract: Background: The bidirectional relationship of asthma and obstructive sleep apnea (OSA) has been confirmed in recent years. However, in the clinical practice, majority of asthma patients did not pay adequate attention to their sleep apnea condition. Berlin questionnaire (BQ) and STOP-Bang questionnaire (SBQ) are two most common OSA screening questionnaires to screen high-risk patients for OSA. This study aimed at evaluating the predictive performance of BQ and SBQ for OSA in asthma patients.Methods: Asthma outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…On the other hand epidemiologic data showed that asthmatic populations have OSA ranges from 38-70% [20]. In a recent prospective study for screening OSA in asthma patients, 63.41% of the subjects have OSA but in asthma accompanied by a rhinitis 85 % have OSA; In this study they specified that 49.59% were mild, 43.9% were moderate 6.5% were severe asthma and mean FEV1 was 87.63 % [21]. In our study according to drug history 72.72% of the ATRD group were taking low dose inhaler steroid combined with longacting beta2 agonist (3'th step to GINA; moderate) others were taking 4'th step (severe), but our all of the AERD patient's treatment were at least 4'th step and 2 of them taking also omalizumab treatment.…”
Section: Discussionmentioning
confidence: 79%
“…On the other hand epidemiologic data showed that asthmatic populations have OSA ranges from 38-70% [20]. In a recent prospective study for screening OSA in asthma patients, 63.41% of the subjects have OSA but in asthma accompanied by a rhinitis 85 % have OSA; In this study they specified that 49.59% were mild, 43.9% were moderate 6.5% were severe asthma and mean FEV1 was 87.63 % [21]. In our study according to drug history 72.72% of the ATRD group were taking low dose inhaler steroid combined with longacting beta2 agonist (3'th step to GINA; moderate) others were taking 4'th step (severe), but our all of the AERD patient's treatment were at least 4'th step and 2 of them taking also omalizumab treatment.…”
Section: Discussionmentioning
confidence: 79%
“…OSA and asthma are both highly prevalent conditions. Epidemiologic data show the prevalence of OSA as high as 70% among asthmatics [14,15]. Asthma and OSA share several risk factors together like obesity, smoking, gastroesophageal reflux, sinoatrial disease and systemic inflammation [16].…”
Section: Discussionmentioning
confidence: 99%
“…Since its introduction by Sullivan in 1981, CPAP has been the main line of treatment for OSA [18]. Growing evidence suggests bidirectional effects of OSA with asthma and better outcomes of asthma treated with CPAP in patients with concomitant OSA [14,[19][20][21]. Effects of asthma on OSA involves mechanical factors (increased airway resistance during REM sleep due to reduction in Functional Residual capacity and End Expiratory Lung Volume leading to upper airway collapse and worsening of apnea), Smoking (directly increasing airway edema and resistance), Corticosteroids use (causing airway myopathy, obesity and airway fat deposition) and increased nasal resistance due to rhinitis or polyps.…”
Section: Discussionmentioning
confidence: 99%
“…Asthma is a chronic inflammatory disorder of the airways leading to hyperresponsiveness with more symptoms at night. High prevalence of OSAS symptoms and moderate‐to‐severe OSAS has been reported in the asthmatic populations . Previous non‐randomized studies showed that continuous positive airway pressure (CPAP) treatment conferred a positive impact on asthma outcomes in patients with concomitant OSAS .…”
Section: Introductionmentioning
confidence: 99%
“…High prevalence of OSAS symptoms and moderate-to-severe OSAS has been reported in the asthmatic populations. [4][5][6][7] Previous nonrandomized studies showed that continuous positive airway pressure (CPAP) treatment conferred a positive impact on asthma outcomes in patients with concomitant OSAS. [8][9][10][11] In this study, we aimed to assess asthma…”
Section: Introductionmentioning
confidence: 99%